Serving the Underserved : Providing Relief to the Displaced Workers in Nepal During the COVID-19 Crisis - Uematsu, Hiroki (World Bank, Washington, DC, 2020)
This note discusses the impacts of Coronavirus (COVID-19) and lockdowns on Nepal’s domestic labor market, using data from the 2017-2018 Nepal Labor Force Survey (NLFS) and the 2018 National Economic Census (NEC). Income relief measures targeted for formal sector firms widely practiced in advanced economies will have limited impacts on saving livelihoods of displaced workers in Nepal. Policy responses should focus on expanding the coverage of social assistance programs or other temporary measures to those who are underserved by the existing programs. These policy interventions need to be accompanied by long-term efforts to set up near real-time monitoring of labor market conditions and establish and maintain core registries of people and businesses so that the government can monitor labor market conditions and deliver relief measures when and where necessary.